Tranexamic Acid for the Prevention of Blood Loss After Cesarean Delivery. Issue 4 (22nd December 2021) - Sentilhes, L.; Sénat, M.V.; Le Lous, M.; Winer, N.; Rozenberg, P.; Kayem, G.; Verspyck, E.; Fuchs, F.; Azria, E.; Gallot, D.; Korb, D.; Desbrière, R.; et al.
Abstract : ( N Engl J Med . 2021;384:1623–1634. doi: 10.1056/NEJMoa2028788. PMID: 33913639) As postpartum hemorrhage (PPH) is a common and potentially deadly complication worldwide, mitigating and reducing the risk of PPH is critical. Tranexamic acid (TXA) has recently been given to reduce postpartum blood loss as it reduces the breakdown of blood clots in the body and slows bleeding, decreasing the risk of adverse outcomes and mortality of hemorrhaging postpartum women. Smaller studies have suggested that prophylactic administration of TXA reduces postpartum blood loss following a cesarean delivery, and this study aims to provide evidence-based conclusions to corroborate those findings.